AN INVESTIGATION OF CAUSAL RELATIONSHIPS BETWEEN GOVERNMENT REVENUE AND EXPENDITURE IN NIGERIA, USING ENGLE COINTEGRATION APPROACH (FUDMA JOURNAL OF SCIENCES, 2022)
This paper investigated the direction of causal relation between Government Revenue and Expenditure in Nigeria using annual data from 1981 to 2020. To validate the existence of long-run and short-run relationships and short-run dynamics of the variables, an Engle Cointegration was employed to test for cointegration and estimate error correction. The hypotheses were examined using the Engle-Granger approach to cointegration. The models' empirical results show that there is bidirectional causality between government revenue and expenditures in Nigeria. This indicates that the government's revenue and expenditure decisions are decided jointly by the country's fiscal authorities. The findings point to the existence of a revenue-to-expenditure feedback system in Nigeria. In other words, both revenue and expenditure levels, affect each other in the Nigerian budgeting process. Therefore, greater tax levels are driven by higher spending levels, and vice versa. This paper recommends that Nigerian fiscal authorities with budget deficits should simultaneously increase revenues and cut expenditure in order to control their deficits
Keywords: Data, long-run, short-run, variables, deficit